Westmount public library: Celebrating 125 years (The Westmount Historian, 2024)
Keywords: Archives; Patrimoine; Vitraux; Westmount

Monuments de changement : les monuments commémoratifs de la Première Guerre mondiale au Québec - Bailey, Caitlin; Regimbald-Roy, Florence (Histoire Québec, 2024)
Keywords: Commémoration; Guerre; Verdun; Westmount

Quand l'art prend la rue - Bilodeau, Maxime (Continuité, 2024)
issued: 2024-23-00
Keywords: Monuments; Places publiques

GARNEAU, DE SAINT-DENYS - Biron, Michel (Dictionnaire biographique du Canada, 2024)

Les peintres de la montée Saint-Michel: un groupe montréalais (1911-1946) - Foisy, Richard (Presses de l'Université de Montréal, 2024)
Keywords: Peintres de la Montée Saint-Michel; Peinture

Searching for Intimacies beyond the Notman Photographs: The Case of Amy Redpath Roddick - Kirkland, Elizabeth; Poutanen, Mary Anne (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Enfants; Femmes; Golden Square Mile; Notman; William; Photographie; Redpath (famille)

Des oeuvres qui transportent - Labrosse, Benoîte (Continuité, 2024)
issued: 2024-23-00
Keywords: Transport en commun

Métro, direction conservation - Lévesque, Jonathan; Senese, Manuela (Continuité, 2024)
issued: 2024-21-00
Keywords: Patrimoine; Transport en commun

Tim Tim? Bwa Chèch! : Documentation de la présence des artistes visuels haïtiens à Montréal 1971-1986 - Theliar-Charles, Kessie (Université Concordia, 2023)
Keywords: Haïtiens

PHILLIPS, MARY MARTHA - McLeod, Ellen Easton (Dictionnaire biographique du Canada, 2023)

John George Savage. Un habitant notable de Dorval/John George Savage. A notable Dorval resident - Nieuwendyk, Dick (Héritage Dorval, 2023)
Keywords: Anglicans; Dorval; Peinture

MUIR, HENRIETTA LOUISE - Roome, Patricia (Dictionnaire biographique du Canada, 2023)

Quand les éléphants s'amenaient dans Rosemont - Delagrave, Louis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Number: 1
Keywords: Cirque; Photographie; Poirier; Conrad

Léon Bellefleur - Guiard, Jean-Paul (Il était une fois...Montréal-Nord, 2022)
issued: 2022-22-00
Keywords: Peinture

Oser sa voix. La galerie Roger Bellemare (1971-2021) - Lacroix, Laurier (Presses de l'Université de Montréal, 2022)
Keywords: Expositions

“Perfect Dry Plates for Canada”: Gelatine Dry-Plate Manufacturing in Canada in the Late Nineteenth Century - Perry, Shannon (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine, 2022)
Keywords: Notman; William; Photographie; Publicité

CULLEN, MAURICE GALBRAITH - Prioul, Didier (Dictionnaire biographique du Canada, 2022)

Femmes et cinéma d'animation: un corpus féministe à l'Office national du film du Canada (1939-1989) - Saint-Pierre, Marie-Josée (Les Presses de l'Université de Montréal, 2022)
OCLC: 1334083138
Keywords: Cinéma; Femmes; Féminisme; Office national du film

Photography: Science, Technology, and Practice in Nineteenth-Century Canada - Schwartz, Joan M. (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine, 2022)
Keywords: Astronomie; Géologie; Notman; William; Photographie

Scott, Brandtner, Eveleigh, Webber: revoir l'abstraction montréalaise des années 1940 - Trépanier, Esther (Presses de l'Université de Montréal, 2022)
Keywords: Peinture

Reclaiming A History: Clay Roots - LeBlanc, Victoria (The Westmount Historian, 2021)
Number: 1
Keywords: Clubs; Femmes; Poterie

DeSerres, une entreprise montréalaise - Bergeron, Normand (Il était une fois...Montréal-Nord, 2021)
issued: 2021-24-00
Keywords: Magasins

Building landscape narratives: the material and visual culture of bridge construction in Montreal, 1854-1930 - Braiden, Heather (Université McGill, 2021)
Keywords: Ponts; Victoria (pont)

Censures et controverses : discours et rapports de forces liés à l'exposition du nu dans l'art montréalais et torontois (1945-1967) - Godin-Laverdière, Julie-Anne (Université du Québec à Montréal, 2021)
Keywords: Expositions

A Heuristic Archive: Jean-Paul Gill's Red Light Photographs - Guillaume, Philippe (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Archives; Patrimoine; Photographie; Quartiers; Saint-Laurent (quartier)

Athanase David et Hector Perrier: la pensée éducative au coeur de l'action politique - Harvey, Fernand (La pensée éducative et les intellectuels au Québec. Les intellectuels nés entre 1850 et 1900, 2021)
Keywords: David; Louis-Athanase; École des Beaux-Arts

Architecture, Photography, and Power: Picturing Montreal, 1973-74 - Imogen Hammond, Cynthia (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Conservation; McConnell; John Wilson; McConnell; John Wilson (maison); Patrimoine; Photographie; Shaughnessy (maison); Van Horne (maison); Van Horne; William

Ateliers à louer, le " phalanstère " d'Alfred Laliberté - Lacroix, Laurier (Les Cahiers des Dix, 2021)
Number: 75
Keywords: Laliberté; Alfred; Locataires; Logement; Peinture; Sculpture

Erase and See: The Photogénie of a Metropolis in Progress - Langford, Martha (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Paysages; Photographie

Re-activations: Alain Chagnon’s Plateau-Mont-Royal in Translation - Langford, Martha (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Photographie; Plateau Mont-Royal; Quartiers

Photogenic Montreal: Activisms and Archives in a Post-Industrial City - Langford, Martha; Sloan, Johanne (McGill-Queen's University Press, 2021)
Keywords: Conservation; Patrimoine; Photographie; Quartiers

Clay Roots: The Potters' Club and its Legacy at the Visual Arts Centre - LeBlanc, Victoria (Visuals Arts Center, 2021)
Keywords: Clubs; Femmes; Poterie

Elites and Scottishness in Montreal: identity, culture and the self in portait photography, 1860-1900 - Regimbald-Roy, Florence (Université McGill, 2021)
Keywords: Notman; William; Photographie; Écossais

McKENZIE, ROBERT TAIT - Roberts, David (Dictionnaire biographique du Canada, 2021)

La représentation de la famille dans la peinture figurative nord-américaine durant la première moitié de la guerre froide (1945-1968) : les cas de Fairfield Porter, d'Alex Colville et de Jean Paul Lemieux - Scott, Christophe (Université du Québec à Montréal, 2021)
Keywords: Famille; Peinture

Through the Lens of Edith Mather: Photographing Demolition and the Transforming City - Southcott, Tanya (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Conservation; Femmes; Patrimoine; Photographie; Rues

The Pastness of Allô Police - Straw, Will (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Criminalité; Photographie

Women in Westmount (The Westmount Historian, 2020)
Number: 2
Keywords: Femmes; Peinture; Élections

CARLI, ALEXANDRE - Carlevaris, Anna Maria (Dictionnaire biographique du Canada, 2020)

HILL, GEORGE WILLIAM - Chagnon, Joanne (Dictionnaire biographique du Canada, 2020)

In search of Expo 67 - Gagnon, Monika Kin; Johnstone, Lesley (McGill-Queen's University Press, 2020)
Keywords: Expositions; Musée d'art contemporain de Montréal

La scène du zine de Montréal : histoire, organisation et position dans le champs culturel - Legendre, Izabeau (Université du Québec à Montréal, 2020)
Keywords: Bande dessinée

Le portrait de Louis Riel par l'abbé Joseph Chabert: à la croisée des destins - Mulaire, Bernard (Cahiers franco-canadiens de l'Ouest, 2020)
Number: 1
Keywords: Chabert; Joseph

Les conditions et les " scènes " de visibilité médiatique lesbienne et féministe: l’atelier de photographie Plessisgraphe des années 70 et 80 - Pidduck, Julianne (Recherches féministes, 2020)
Number: 2
Keywords: Femmes; Féminisme; Photographie

Une amitié nécessaire: entraide et fraternité dans le champ des comic books québécois (1984-1995) - Rioux, Philippe (Cahiers de la Société bibliographique du Canada / Papers of the Bibliographical Society of Canada, 2020)
Keywords: Bande dessinée; Librairie; Magasins; Édition

CHARLEBOIS, JOSEPH - Sicotte, Hélène (Dictionnaire biographique du Canada, 2020)

HOMIER, JOSEPH-ARTHUR - Turner, D.J. (Dictionnaire biographique du Canada, 2020)

Arts visuels du Plateau (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2019)
issued: 2019-21-00
Keywords: Arts sacrés; Borduas; Paul-Émile; Graff; Gravure; Peinture; École des Beaux-Arts

Le champ des décors polychromes dans les églises au Québec entre 1850 et 1930 - Bellerose, Véronique (Université du Québec à Montréal, 2019)
Keywords: Arts sacrés; Bourassa; Napoléon; Leduc; Ozias; Peinture; Églises

Les impacts du contexte canadien de la Deuxième Guerre mondiale sur l'Art Association of Montreal - Boisclair, Rachel (Université du Québec à Montréal, 2019)
Keywords: Art association; Guerre; Musée des Beaux-Arts; Musées

Aux portes du passé - Duff, Jocelyn (Continuité, 2019)
issued: 2019-23-00
Keywords: Autochtones; Communautés religieuses; La Visitation (église); Liébert; Philippe; Missions; Sculpture; Églises

Les portes de la sacristie de l'église de la Visitation et la mission d'évangélisation des Autochtones - Duff, Jocelyn (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2019)
Number: 5
Keywords: Autochtones; Communautés religieuses; La Visitation (église); Liébert; Philippe; Missions; Sculpture; Églises

Le " Michel-Ange de Montréal ": Guido Nincheri - Grondin, Mélanie (Cap-aux-Diamants, 2019)
issued: 2019-23-00
Keywords: Arts sacrés; Italiens; Peinture; Vitraux; Églises

The Women's Art Society of Montreal and its place in history, 1894-2019 - Keays, Cathy (Artists in Montreal, 2019)
OCLC: 1200841549
Keywords: Femmes

La Revue moderne : les représentations iconographiques d'un magazine féminin, 1919-1938 - Perreault, Anouk (Université du Québec à Montréal, 2019)
Keywords: Femmes; Photographie; Revue moderne (La)

Le rôle de l'art contemporain dans les jardins du Québec et sa mise en valeur : une étude comparative - Rondeau, Ariel (Université du Québec à Montréal, 2019)
Keywords: Jardin botanique; Jardins

L'art de la gravure entre 1850 et 1885 et l'architecture commerciale de Montréal : le cas de John Henry Walker - Sirois, Hélène (Université du Québec à Montréal, 2019)
Keywords: Gravure; Publicité; Walker; John Henry

HAMMOND, JOHN - Tisdale, Jane (Dictionnaire biographique du Canada, 2019)

Gabor Szilasi: le monde de l'art à Montréal 1960-1980 - Tousignant, Zoë (McCord Museum, 2019)
OCLC: 1112064957
Keywords: Expositions; Musée McCord; Photographie

Reinforcing racial hierarchy through visual culture : black enslaved children in New France and early Quebec (1700-1834) - Trahan-Thomassin, Marilou (Université McGill, 2019)
Keywords: Enfants; Esclaves; Noirs; Peinture; Publicité

De la Toscane au Canada, les statuaires italiens - Tremblay, Marc Alain; Carli-Trudeau, Jocelyne F. (Cap-aux-Diamants, 2019)
issued: 2019-23-00
Keywords: Arts sacrés; Italiens; Sculpture

Hommage à Pierre Dansereau (Mémoire vivante, 2018)
issued: 2018/2019
Keywords: Cinéma; Hommes d'affaires; Incendies; Laurier Palace; Lawand Amusement Company Limited; Mouleurs; Outremont; Peinture; Quartiers

Patrimoine religieux (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2018)
issued: 2018-23-00
Keywords: Académie Marie-Rose; Arts sacrés; Carmélites; Communautés religieuses; Conservation; Juifs; Patrimoine; Plateau Mont-Royal; Protestants; Quartiers; Sculpture; Églises

Les caricatures d'Albéric Bourgeois durant la Seconde Guerre mondiale - Aird, Robert (Cap-aux-Diamants, 2018)
issued: 2018-21-00
Keywords: Bourgeois; Albéric; Caricature

Edmond-Joseph Massicotte. Dessinateur de presse et caricaturiste - Beaulieu, Anne-Philippe (Cap-aux-Diamants, 2018)
issued: 2018-21-00
Keywords: Caricature; Massicoote; Edmond-Joseph

La profession de dessinateur de presse au Canada français au tournant du XXe siècle: le cas d’Edmond-Joseph Massicotte (1875-1929) - Beaulieu, Anne-Philippe (Université de Montréal, 2018)
Keywords: Caricature; Massicotte; Edmond-Joseph

Van Horne and Friends: Collecting European Art in Montreal’s Square Mile - Brooke, Janet M. (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Van Horne et ses amis: Collectionner l’art européen dans le Mille carré de Montréal - Brooke, Janet M. (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Clubs, Axes, and Umbrellas: The Woman Suffrage Movement as Seen by Montreal Cartoonists (1910-1914) - Chemartin, Pierre; Pelletier, Louis (McGill-Queen's University Press, 2018)
Keywords: Caricature; Femmes; Élections

L'affiche, une présence vivante dans la ville - Choko, Marc H. (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)
Keywords: Canadien Pacifique; Publicité; École des Beaux-Arts

Le dessinateur breton Théophile Busnel au Québec: interactions artistiques avec Albéric Bourgeois - Danaux, Stéphanie (Voix et Images, 2018)
Number: 2
Keywords: Caricature; Patrie (La)

Anti-Semitic Caricature in 1930s Montreal: Language and National Stereotypes in Adrien Arcand’s Le Goglu (1929-1933) - Desforges, Josée (McGill-Queen's University Press, 2018)
Keywords: Arcand; Adrien; Caricature; Idéologies

Un vieux de '37 d'Henri Julien - Droüin, François (Cap-aux-Diamants, 2018)
issued: 2018-21-00
Keywords: Julien; Henri; Peinture

Envisioning new futures: Portrait photographs of black Victorians in Montreal, 1861-1901 - Evoughlian, Sandra (Université McGill, 2018)
Keywords: Noirs; Notman; William; Photographie

Françoise Sullivan. Sa vie et son oeuvre - Gérin, Annie (Arts Canada Institute / Institut de l'art canadien, 2018)
Keywords: Danse; Peinture; Sculpture

Obsession: Les céramiques japonaises de Sir William Van Horne - Graham, Ron (McGill-Queen's University Press, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Obsession: Sir William Van Horne's Japanese Ceramics - Graham, Ron (McGill-Queen's University Press, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Crossing the Line: Canadian Satire of the "Pretty Girl" North and South of the 49th Parallel - Grove, Jaleen (Sketches from An Unquiet Country, 2018)
Keywords: Caricature; Femmes

Frankenstein’s Tory: Graphic Satire in 1840s Montreal, from Le Charivari canadien to Punch in Canada - Hardy, Dominic (McGill-Queen's University Press, 2018)
Keywords: Caricature; Humour

Sketches from An Unquiet Country - Hardy, Dominic; Gérin, Annie; Senechal Carney, Lora (McGill-Queen's University Press, 2018)
Keywords: Bourgeois; Albéric; Caricature; Humour; Idéologies; Julien; Henri; Walker; John Henry

La bande dessinée québécoise: sous la plume des pionniers et des contemporains - Jacob, Carmélie; Saouter, Catherine (Voix et Images, 2018)
Number: 2
Keywords: Bande dessinée

Albéric Bourgeois … a.k.a. Baptiste Ladébauche - Lacroix, Laurier (McGill-Queen's University Press, 2018)
Keywords: Bourgeois; Albéric; Canard (Le); Caricature

SUZOR-COTÉ, MARC-AURÈLE DE FOY - Lacroix, Laurier (Dictionnaire biographique du Canada, 2018)

Bourassa et Lévesque. Marketing de raison contre marketing de passion - Lavigne, Alain (Septentrion, 2018)
Keywords: Bourassa; Robert; Caricature; Journalistes; Lévesque; René; Élections

Le bâtisseur de nation - Newman, Peter C. (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

The Nation Builder - Newman, Peter C. (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Onésime par Albert Chartier: analyse d'une bande dessinée québécoise aux influences américaines - Pétrin, Alexandre (Université du Québec à Trois-Rivières, 2018)
Keywords: Bande dessinée; Caricature

Case Studies - Takesue, Akiko (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Catalogue des céramiques - Takesue, Akiko (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Ceramics Catalogue - Takesue, Akiko (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Études de cas - Takesue, Akiko (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

La "vie sociale" de la collection de céramiques japonaises de Van Horne - Takesue, Akiko (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Les carnets de Van Horne - Takesue, Akiko (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

The “Social Life” of the Van Horne Japanese Ceramic Collection - Takesue, Akiko (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Van Horne’s Notebooks - Takesue, Akiko (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

La ville en temps de crise. Montréal et les peintres juifs - Trépanier, Esther (Les médias parlent et chantent. Chroniques de la vie culturelle à Montréal durant la crise et la guerre, 2018)
Keywords: Guerre; Juifs; Pauvreté; Peinture

Uncle Sam, A Not-So-Distant Cousin: Canadian Contributions to the Genesis of a US Allegorical Figure - Vachon, Christian (Sketches from An Unquiet Country, 2018)
Keywords: Caricature; Julien; Henri; Walker; John Henry

Japan Contained: The Birth of the Asian Collections at the Montreal Museum of Fine Arts - Vigo, Laura (Obsession: Sir William Van Horne's Japanese Ceramics, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Le Japon contenu: La naissance des collections asiatiques au Musée des beaux-arts de Montréal - Vigo, Laura (Obsession: Les céramiques japonaises de Sir William Van Horne, 2018)
Keywords: Canadien Pacifique; Hommes d'affaires; Musée des Beaux-Arts; Musées; Poterie; Van Horne; William

Trajectoires fluides et croisements lumineux : histoire du verre d’art au Québec dans le contexte d’Expo 67 - Andrus, Bruno Victor (Université Concordia, 2017)
Keywords: Vitraux; École du meuble

Judith en 1951: le statut de l’infigurable dans l’oeuvre d’Ozias Leduc - Bois, Mathilde (Études d'histoire religieuse, 2017)
Number: 1-2
Keywords: Leduc; Ozias

Faire place. Une brève histoire des arts plastiques à l'Université de Montréal - Boucher, Flavie; Fiset, Daniel (Centre d'exposition de l'Université de Montréal, 2017)
Keywords: Université de Montréal

Why the Flapper Still Matters: Feminist Pedagogy, the Modern Girl, and the Women Artists of the Beaver Hall Group - Burr, Christina Ann (Revue d'histoire de l'éducation / Historical Studies in Education, 2017)
issued: 2017-23-00
Keywords: Clubs; Femmes; Peinture

Guido Nincheri: le savoir-faire de la Renaissance italienne à Montréal - Busseau, Laurent (Histoire Québec, 2017)
Number: 4
Keywords: Arts sacrés; Peinture; Vitraux; Églises

La mythologie gréco-romaine dans l'oeuvre profane de Guido Nincheri (1920-1930) - Busseau, Laurent (Histoire Québec, 2017)
Number: 1
Keywords: Peinture; Vitraux

Les acquisitions du Musée d'art contemporain de Montréal 1992-2012 - Dubreuil, Martine (Université de Montréal, 2017)
Keywords: Expositions; Musée d’art contemporain de Montréal; Musées

The Art and Passion of Guido Nincheri - Grondin, Mélanie (Véhicule Press, 2017)
Keywords: Arts sacrés; Peinture; Vitraux; Églises

L’ancien square Dominion à Montréal: un parcours d’art et d’histoire - Joly, Diane (Histoire Québec, 2017)
Number: 4
Keywords: Dominion (square); Idéologies; Monuments; Places publiques; Squares

De l’illustration à la sculpture : Maria Chapdelaine, source d’inspiration de Suzor-Coté - Lacroix, Laurier (Les Cahiers des Dix, 2017)
Number: 71
Keywords: Art association; Musées; Roman; Sculpture

Ludger Larose. Un artiste engagé au tournant du 20e siècle - Longstaff, Alison (Les Presses de l'Université Laval, 2017)
Keywords: Bourgeoisie; Francs-Maçons; Peinture

Vision chromatique et gestualité : le concept de transparence dans les oeuvres de Marcelle Ferron - Millet, Véronique (Université du Québec à Montréal, 2017)
Keywords: Automatistes; Vitraux

La bande dessinée féministe humoristique au cours des décennies 1970 et 1980 au Québec: l'humour visuel comme outil d'appropriation des représentations - Santerre, Hugo (Université du Québec à Montréal, 2017)
Keywords: Bande dessinée; Caricature; Femmes; Féminisme; Humour

Les planches de bande dessinée de Pierre Dupras publiées dans le journal Québec-Presse (1969-1974): contexte et analyse - St-Cerny-Gosselin, Camille (Université du Québec à Montréal, 2017)
Keywords: Bande dessinée; Caricature

Entre passion et raison : une histoire du collectionnement privé à Montréal (1850-1910) - Truchon, Caroline (Université de Montréal, 2017)
Keywords: Expositions; Musées

Entre la fuite et l'exil: réception, circulation et reconnaissance des artistes non figuratifs du Québec au Musée des beaux-arts de Montréal, au Musée de la Province et à la Galerie nationale du Canada (1955-1960) - Blanchard Pilon, Jacinthe (Université du Québec à Montréal, 2016)
Keywords: Musée des Beaux-Arts; Musées

Le souffle et la flamme: Marie-Alain Couturier au Canada et ses lettres à Louise Gadbois - Brunet-Winmann, Monique (Septentrion, 2016)
Keywords: Arts sacrés; Couturier; Marie-Alain

''Une grande fête canadienne'': les Autochtones et le programme Arts et culture des Jeux olympiques de Montréal - Bureau-Capuano, Mélissa (Les Cahiers d'histoire, 2016)
issued: 2016-23-00
Keywords: Autochtones

Un nouveau souffle pour la Biennale de Montréal? Une analyse comparée avec les grandes biennales internationales d'art contemporain - Chouinard, Clara (Université de Montréal, 2016)
Keywords: Expositions; Musée d’art contemporain de Montréal; Musées

1920s Modernism in Montreal. The Beaver Hall Group - Des Rochers, Jacques; Foss, Brian (Musée des beaux-arts de Montréal et Black dog Publishing, 2016)
Translators: _:n45476
Keywords: Clubs; Peinture

Defining the Beaver Hall Group Today - Des Rochers, Jacques (1920s Modernism in Montreal. The Beaver Hall Group, 2016)
Translators: _:n45496
Keywords: Clubs; Peinture

Setting the Stage: The Emergence of the Beaver Hall Group - Des Rochers, Jacques (1920s Modernism in Montreal. The Beaver Hall Group, 2016)
Translators: _:n45644
Keywords: Clubs; Peinture

The Beaver Hall Group: A Much Anticipated Re-reading - Des Rochers, Jacques (1920s Modernism in Montreal. The Beaver Hall Group, 2016)
Translators: _:n45686
Keywords: Clubs; Peinture

La vie et l'oeuvre de Maurice Day, artiste visuel pointelier - Desjardins, Pierre (Atelier d'histoire de la Pointe-aux-Trembles, 2016)

Out on the Town: Modernism, Arts and Entertainment in Montreal, 1920-33 - Foss, Brian (1920s Modernism in Montreal. The Beaver Hall Group, 2016)
Translators: _:n45561

L'ordre social dans les représentations promotionnelles de la Banque d'Épargne, diffusées sous l'égide de la Société Saint-Jean-Baptiste de Montréal entre 1924 et 1946 - Hazan, Olga (Étude d'histoire religieuse, 2016)
Number: 1-2
Keywords: Banque d'Épargne de la cité et du district de Montréal; Peinture; Publicité; Société Saint-Jean-Baptiste

Trajectoires et subjectivités italo-québécoises : le processus identitaire de la deuxième génération tel que conçu par Marco Micone, Mary Melfi et Paul Tana - Hélie-Martel, Anaïs (Université de Montréal, 2016)
Keywords: Cinéma; Italiens; Langue; Roman; Théâtre

''As well as men'': The Gendering of Beaver Hall - Huneault, Kristina (1920s Modernism in Montreal. The Beaver Hall Group, 2016)
Translators: _:n44623
Keywords: Clubs; Femmes; Peinture

LActuelle à toute vitesse - Lamarche, Lise (L'Actuelle. Une galerie d'art non figuratif 1955-1957, 2016)
Keywords: Expositions; Peinture; Sculpture

L'Actuelle. Une galerie d'art non figuratif 1955-1957 - Lamarche, Lise; Daigneault, Gilles; Bouraly, Lisa (Éditions du Passage et Fondation Guido Molinari, 2016)
Translators: _:n48356
Keywords: Expositions; Peinture; Sculpture

LActuelle. Une chronologie (1955-1957) - Lamarche, Lise; Daigneault, Gilles; Bouraly, Lisa (L'Actuelle. Une galerie d'art non figuratif 1955-1957, 2016)
Keywords: Expositions; Peinture; Sculpture

William Notman's Home Library: Discovering Underlying Meaning in the Portrait Photograph - Lerner, Loren (À la recherche du savoir: Nouveaux échanges sur les collections du Musée McCord / Collecting Knowledge: New Dialogues on McCord Museum, 2016)
Keywords: Notman; William; Photographie

Slavery, Geography and Empire in Nineteenth-Century Marine Landscapes of Montreal and Jamaica - Nelson, Charmaine A. (Routledge, 2016)
Keywords: Africains; Esclaves; Noirs; Paysages; Peinture

Julien Hébert, fondateur du design moderne au Québec - Racine, Martin (Éditions du Passage, 2016)

A Locational History of Fashion in Montréal - Sark, Katrina; Bélanger-Michaud, Sara Danièle (University of Chicago Press, 2016)
Keywords: Cinéma; Confection; Costume; Expositions; Musique; Musée McCord; Musée des Beaux-Arts; Musées; Vêtements

The Intersecting Paths of Budding Artists - Sicotte, Hélène (1920s Modernism in Montreal. The Beaver Hall Group, 2016)
Translators: _:n45573

Mainmise, Québec-Presse et les revues de bande dessinée - St-Cerny Gosselin, Camille (La contre-culture au Québec, 2016)
Keywords: Bande dessinée

Au coeur du monde industriel de son temps: Adrien Hébert dans le port de Montréal - Trépanier, Esther (Bulletin de l'Association québécoise pour le patrimoine industriel, 2016)
issued: 2016-23-00
Keywords: Hébert; Adrien; Peinture; Port

The Beaver Hall Group: A Montreal Modernity - Trépanier, Esther (1920s Modernism in Montreal. The Beaver Hall Group, 2016)
Translators: _:n45467
Keywords: Clubs; Peinture

Baptiste Ladébauche, du folklore au cabaret: à propos des collaborations d'Albéric Bourgeois et de Charles Marchand dans les années 1920 - Bellemare, Luc (Quand la caricature sort du journal: Baptiste Ladébauche, 1878-1957, 2015)
Keywords: Bourgeois; Albéric; Cabarets; Caricature; Chanson; Musique

De l'autoportrait à l'autofiction dans l'oeuvre sculpté et les écrits d'Alfred Laliberté - Bergeron, Maggy (Université Laval, 2015)
Keywords: Expositions; Laliberté; Alfred; Musée des Beaux-Arts; Musées; Sculpture

De Saint-Denys Garneau, biographie - Biron, Michel (Boréal, 2015)
Keywords: de Saint-Denys Garneau; Hector; Écrivains

Les Voyages autour du monde de Ladébauche, d'Hector Berthelot à Albéric Bourgeois. Récits de voyage et langue vernaculaire - Cambron, Micheline (Quand la caricature sort du journal: Baptiste Ladébauche, 1878-1957, 2015)
Keywords: Berthelot; Hector; Bourgeois; Albéric; Canard (Le); Caricature

Plier le temps, déplier la carte. Les Mystères de Montréal par M. Ladébauche d'Hector Berthelot - Charlier, Marie-Astrid (Quand la caricature sort du journal: Baptiste Ladébauche, 1878-1957, 2015)
Keywords: Berthelot; Hector; Caricature; Humour

Une modernité des années 1920 à Montréal. Le groupe de Beaver Hall - Des Rochers, Jacques; Foss, Brian (Musée des beaux-arts de Montréal et Black dog Publishing, 2015)
Translators: _:n45485
Keywords: Clubs; Peinture

Les voyages de Ladébauche autour du monde d'Albéric Bourgeois: un art entre illustration et satire graphique - Danaux, Stéphanie (Quand la caricature sort du journal: Baptiste Ladébauche, 1878-1957, 2015)
Keywords: Bourgeois; Albéric; Caricature; Humour

Un patrimoine artistique atypique. Les croix et la signalétique - Déom, Claudine; Doucet, Danielle (ARQ - Architecture Québec, 2015)
Number: 172
Keywords: Patrimoine

La conservation des oeuvres. Quelques études de cas - Déom, Claudine; Tessier, Stéphane (ARQ - Architecture Québec, 2015)
Number: 172
Keywords: Conservation

Circonscrire aujourd'hui le Groupe de Beaver Hall - Des Rochers, Jacques (Une modernité des années 1920 à Montréal. Le groupe de Beaver Hall, 2015)
Translators: _:n45619
Keywords: Clubs; Peinture

Le contexte qui a vu naître le Groupe de Beaver Hall - Des Rochers, Jacques (Une modernité des années 1920 à Montréal. Le groupe de Beaver Hall, 2015)
Translators: _:n45443
Keywords: Clubs; Peinture

Le Groupe de Beaver Hall: une relecture attendue - Des Rochers, Jacques (Une modernité des années 1920 à Montréal. Le groupe de Beaver Hall, 2015)
Translators: _:n45513
Keywords: Clubs; Peinture

Lorsque Ladébauche rencontre l'Iroquois du Monument à Maisonneuve - Desforges, Josée (Quand la caricature sort du journal: Baptiste Ladébauche, 1878-1957, 2015)
Keywords: Autochtones; Caricature; Chomedey de Maisonneuve; Paul (Maisonneuve; Paul de Chomedey de); Histoire; Iroquois; Monuments

Premiers regards sur les oeuvres d'art de la CSDM: Une histoire de commandes, de courants artistiques, de matérialités, d'intégrations - Doucet, Danielle (ARQ - Architecture Québec, 2015)
Number: 172

Sortir en ville: modernité, arts et spectacles à Montréal, 1920-1933 - Foss, Brian (Une modernité des années 1920 à Montréal. Le groupe de Beaver Hall, 2015)
Translators: _:n45703

Qui est Catherine Ladébauche? - Godin-Laverdière, Julie-Anne (Quand la caricature sort du journal: Baptiste Ladébauche, 1878-1957, 2015)
Keywords: Caricature; Femmes

1916. Enfin l'Album Henri Julien - Hardy, Dominic (De la Belle époque à la Crise. Chroniques de la vie culturelle à Montréal, 2015)
Keywords: Caricature; Julien; Henri

À la découverte du Fonds Albéric Bourgeois (1876-1962): thématiques d'une société en transformation, 1899-1957 - Hardy, Dominic; Godin-Laverdière, Julie-Anne; Perron, Nancy (Quand la caricature sort du journal: Baptiste Ladébauche, 1878-1957, 2015)
Keywords: Archives; Bourgeois; Albéric; Caricature; Histoire

''Aussi bien que des hommes'' Le Groupe de Beaver Hall au prisme du genre - Huneault, Kristina (Une modernité des années 1920 à Montréal. Le groupe de Beaver Hall, 2015)
Translators: _:n44661
Keywords: Clubs; Femmes; Peinture

Frédéric Back. La capacité d'enchanter - Jasmin-Bélisle, Hélène (Lidec, 2015)
Keywords: Peinture

Canadian Innovator in Modern Architectural Stained Glass: Marcelle Ferron - Kranias, Kathy (Journal of the Society for the Study of Architecture in Canada / Journal de la société pour l'étude de l'architecture au Canada, 2015)
Number: 2
Keywords: Peinture; Sculpture; Vitraux

Visions of Canada: Photographs and History in a Museum, 1921-1967 - McNabb, Heather (Université Concordia, 2015)
Keywords: Histoire; Musée McCord; Musées; Photographie

Quand la caricature sort du journal: Baptiste Ladébauche, 1878-1957 - Cambron, Micheline; Hardy, Dominic (Fides, 2015)
Keywords: Berthelot; Hector; Bourgeois; Albéric; Caricature; Humour

Les chemins croisés de la formation artistique - Sicotte, Hélène (Une modernité des années 1920 à Montréal. Le groupe de Beaver Hall, 2015)
Translators: _:n45718

''Born with a Silver Spoon and Fork'': Photographic Testimonies of Acculturation, Montreal, 1873 - Stanworth, Karen (Visibly Canadian: Imaging Collectives Identities in the Canadas, 1820-1910, 2015)
Keywords: Bute House (école protestante); Femmes; Photographie; Protestants

Des caricatures antisémites: la propagande d'Adrien Arcand - Tremblay, Marie-Soleil (Histoire Québec, 2015)
Number: 3
Keywords: Arcand; Adrien; Caricature; Fasciste canadien (Le); Idéologies; Juifs; Partis politiques

1920. Création du groupe de Beaver Hall. Des femmes font jazzer la couleur - Trépanier, Esther (De la Belle époque à la Crise. Chroniques de la vie culturelle à Montréal, 2015)
Keywords: Clubs; Femmes; Peinture

Le Groupe de Beaver Hall: une modernité montréalaise - Trépanier, Esther (Une modernité des années 1920 à Montréal. Le groupe de Beaver Hall, 2015)
Translators: _:n45667
Keywords: Clubs; Peinture

Robert La Palme et les origines caricaturales de la Grande Noirceur duplessiste: conception et diffusion d'une mythistoire au Québec, des années 1940 à nos jours - Turgeon, Alexandre (Université Laval, 2015)
Keywords: Caricature

1912. '' the best that brains and money can provide''. The Montreal Art Gallery - Vanlaethem, France (De la Belle époque à la Crise. Chroniques de la vie culturelle à Montréal, 2015)
Keywords: Musée des Beaux-Arts; Musées

Profil économique de William Notman. Bilan des connaissances - Beaulieu, Marion (Laboratoire d'histoire et de patrimoine de Montréal, 2014)
Keywords: Notman; William; Photographie

The Stained Glass of the Hosmer Collection, McGill University - Bugslag, James; Isler-de-Jongh, Ariane (McGill-Queen's University Press, 2014)
Keywords: Université McGill; Vitraux

Nouveaux Molinarismes - Carruthers, Meredith (Une banque dans Hochelaga - l'immeuble de la Fondation Guido Molinari, 2014)
Keywords: Banque d'épargne de la cité et du district de Montréal; Banques; Hochelaga (quartier); Quartiers

Égrégore: une histoire du mouvement automatiste de Montréal - Ellenwood, Ray (Kétoupa Édition et Les Éditions du Passage, 2014)
Translators: _:n45592
Keywords: Automatistes

À propos de Jean Chauvin (1895-1958) et de son livre Ateliers (1928) - Lacroix, Laurier (Les Cahiers des Dix, 2014)
Number: 68
Keywords: Journalistes; Peinture; Sculpture

Identité graphique - Lapointe, Louis (Continuité, 2014)
issued: 2014-22-00

I don't: The Commodification of the Bride in Montreal Art from the 1970s - Stratica Mihail, Eliana (Université Concordia, 2014)
Keywords: Femmes; Féminisme; Mariage

La Palme présente Displicuit Nasus Tuus: quand la caricature sert de discours politique au Québec - Turgeon, Alexandre (Journal of the Canadian Historical Association / Revue de la société historique du Canada, 2014)
Number: 1
Keywords: Caricature

Fernand Leduc et l'automatisme - Viau, René (Montréal en tête, 2014)
issued: 2014-23-00
Keywords: Automatistes; Borduas; Paul-Émile; Idéologies; Peinture

Le Plateau: carrefour des arts (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2013)
issued: 2013-23-00
Keywords: Chanson; Cinéma; Musique; Orchestre symphonique de Montréal; Peinture; Plateau Mont-Royal; Quartiers; Théâtre; Théâtre du Rideau vert; École Le Plateau

Qui a eu cette idée folle un jour d'inventer l'école? (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2013)
issued: 2013-22-00
Keywords: Juifs; Plateau Mont-Royal; Quartiers

The Likeness of Fugitivity: William Notman's Carte-de-visite Portrait of John Anderson - Boone, Emilie (History of Photography, 2013)
Number: 2
Keywords: Notman; William; Photographie

Émergence et évolution d’une profession artistique: les dessinateurs de presse entre 1880 et 1914 à Montréal - Danaux, Stéphanie (Médias 19, 2013)
Keywords: Caricature; Gravure; Patrie (La)

L'iconographie d'une littérature: évolution et singularités du livre illustré francophone au Québec, 1840-1940 - Danaux, Stéphanie (Presses de l'Université Laval, 2013)
Keywords: Édition

Sulpician Cultural Strategies: The Fine Arts - Des Rochers, Jacques (The Sulpicians of Montreal: a history of power and discretion, 1657-2007, 2013)
Translators: _:n46706
Keywords: Communautés religieuses; Sulpiciens

Dessins de voyage - Drouin, Daniel (Continuité, 2013)
issued: 2013-23-00

Esthétique de la typographie: Roland Giguère, les Éditions Erta et l'École des arts graphiques - Dulude, Sébastien (Nota Bene, 2013)
Keywords: École des arts graphiques; Édition

Maurice Le Bel, graveur et peintre: du terroir à l'abstraction - Foisy, Richard (Fides, 2013)
Keywords: Gravure; Peinture

Halte-là le Canadien est là: analyse socio-sporto-culturelle de la série Bleu-Blanc-Rouge (1969-1979) de Serge Lemoyne (1941-1998) - Fortier, Nadège (Université du Québec à Montréal, 2013)
Keywords: Canadien (Club de hockey); Hockey

Materiality and "l'art intégré": Charles Daudelin's Art in the Urban Context - Fortin, Damien (Université Concordia, 2013)

Paul-Émile Borduas : a critical biography - Gagnon, François-Marc (McGill-Queen's University Press, 2013)
Translators: _:n48921
Keywords: Borduas; Paul-Émile; Peinture; Sculpture

Montréal érotique : pin-up et imagerie de nus chez le photographe de presse Conrad Poirier, 1912-1968 - Godin-Laverdière, Julie-Anne (Revue de Bibliothèque et Archives nationale du Québec, 2013)
Keywords: Photographie; Poirier; Conrad

Le discours muséal à travers l'exposition des collections de quatre musées d'art: Montréal, Québec, Joliette et Sherbrooke - Houle, Nathalie (Université de Montréal, 2013)
Keywords: Expositions; Musée des Beaux-Arts; Musées

William Notman et les imaginaires photographiques de la chasse au XIXe siècle à Montréal - Lahaie, Andréann (Université du Québec à Montréal, 2013)
Keywords: Notman; William; Photographie

Les années Croc: l'histoire du magazine qu'on riait - Leduc, Jean-Dominic; Viau, Michel (Québec Amérique, 2013)
Keywords: Caricature; Humour

Où en sommes-nous avec l'art féministe? Analyse de la programmation de la Centrale Galerie Powerhouse (1973-1978 et 2007-2010) - Rondeau, Kim (Université du Québec à Montréal, 2013)
Keywords: Expositions; Femmes; Féminisme

L'Ecole des Beaux-Arts de Nantes et la fondation des Ecoles des Beaux-Arts de Québec et de Montréal: 1900-1948 - Souty, François (Les échanges culturels internationaux: France, Brésil, Canada-Québec, 2013)
Keywords: Français; École des Beaux-Arts

La Revue populaire et Le Samedi – Objets de diffusion de la modernité photographique au Québec, 1935-1945 - Tousigant, Zoë (Revue de Bibliothèque et Archives nationale du Québec, 2013)
Keywords: Photographie

La bourgeoisie en portrait au Bas-Canada (1790-1830) - Bernier, Geneviève (Université Laval, 2012)
Keywords: Bourgeoisie; Peinture

Le graffiti à Montréal: pratique machiste et stratégies féminines - Couvrette, Katrine (Université de Montréal, 2012)

Entre création et destruction: les comportements des types du juif et du canadien français dans les caricatures antisémites publiées par Adrien Arcand à Montréal entre 1929 et 1939 - Desforges, Josée (Université du Québec à Montréal, 2012)
Keywords: Arcand; Adrien; Caricature; Fasciste canadien (Le); Idéologies; Juifs; Partis politiques

Publicité Sauvage. 25 ans et demi - H. Choko, Marc (Infopresse, 2012)
Keywords: Publicité

Un valentin au grand Maurice- Léon Bloy, Olivar Asselin et Robert La Palme: essai sur un problème de transfert culturel dans l'histoire de la caricature au Québec - Hardy, Dominic (Mens, 2012)
issued: 2012-21-00
Keywords: Asselin; Olivar; Caricature; Journalistes

Un trésor à conserver - Jalbert, Isabelle (Publicité Sauvage. 25 ans et demi, 2012)
Keywords: Publicité

Hypothèses d'amarrages, une intervention artistique à Montréal: contribution à l'esthétique et à la politique du paysage urbain - Lafontaine, Simon (Université du Québec à Montréal, 2012)

Un visa chrétien pour l'art abstrait et pour un affranchissement. Marie Alain Couturier, o.p. au Québec (1940-1945) - Lamonde, Yvan (Voix et Images, 2012)
issued: 2012-24-00
Keywords: Couturier; Marie-Alain; Peinture

Between the Lines: Interartistic Modernism in Canada, 1930-1960 - Rackham, Michèle (Université McGill, 2012)
Keywords: Peinture; Poésie; Sculpture

De l'information sur le Québec underground, 1962-1972 / Information from the Quebec underground, 1962-1972 - Tayler, Felicity (Des actions parlantes. Aspects de la culture québécoise des années 1960 et 1970 / Actions that speaks. Aspects of Quebec Culture in the 1960s and 1970s, 2012)

LES 25 ANS et demi DE PUBLICITÉ SAUVAGE - Turenne, Martine (Publicité Sauvage. 25 ans et demi, 2012)
Keywords: Publicité

Napoléon Bourassa: témoignage photographique - Béland, Mario (Continuité, 2011)
issued: 2011-24-00/2012-24-00
Keywords: Bourassa; Napoléon; Peinture; Photographie

Marcel Brisebois et le Musée d'art contemporain de Montréal (1985-2004) - Chassé, Bernard; Lapierre, Laurent (Presses de l'Université du Québec et Chaire de leadership Pierre Péladeau, 2011)
Keywords: Musée d’art contemporain de Montréal; Musées

Les monuments funéraires des Hébert au cimetière Notre-Dame-des-Neiges - Drouin, Daniel; Ouellet, Pierre-Olivier (Éditions de la Fabrique de la paroisse Notre-Dame de Montréal, 2011)
Keywords: Cimetières; Hébert; Henri; Hébert; Philippe; Monuments; Sculpture

Les Salons parisiens au Canada: L'Exposition d'art français de Montréal en 1909 - Gauthier, Marc (Université Laval, 2011)
Keywords: Expositions; Français

La chapelle Notre-Dame-De-Lourdes de Montréal: histoire, composition et fonction du décor intérieur - Giguère, Vincent (Université Laval, 2011)
Keywords: Arts sacrés; Notre-Dame-de-Lourdes (chapelle); Églises

Emmanuel Briffa: l’homme des théâtres - Labrecque, Jérôme (Continuité, 2011)
issued: 2011-22-00
Keywords: Théâtre

Le parcours de formation et les stratégies de diffusion de femmes galeristes à Montréal entre 1941 et 1963: Denyse Delrue, Estelle Hecht, Agnes Lefort et Rose Millman - Lafleur, Geneviève (Université du Québec à Montréal, 2011)
Keywords: Expositions; Femmes; Peinture

L'ultime expérience de détachement: Borduas à Paris en 1955 - Lapointe, Gilles (Bulletin d'histoire politique, 2011)
issued: 2011-23-00
Keywords: Borduas; Paul-Émile; Peinture

Signé Brunet: la contribution du sculpteur Émile Brunet à l'art funéraire du Cimetière Notre-Dame-des-Neiges - Laroche, Ginette (Éditions de la Fabrique de la paroisse Notre-Dame de Montréal, 2011)
Keywords: Cimetières; Notre-Dame-des-Neiges (cimetière); Sculpture

Historique de Skol, 1984-1995 - Théoret, Yves; Proulx, Anne-Marie; Russo, Sabrina (Centre des arts actuels Skol, 2011)

The Surrender of Montreal to General Amherst de Francis Hayman et l'identité impériale britannique - Turcot, Laurent (Mens, 2011)
issued: 2011-23-00
Keywords: Capitulation; Guerre; Peinture

Savoir se passer du présent – savoir ce passé du futur. Les caricatures de Robert La Palme du 29 mai 1956 - Turgeon, Alexandre (Recherches sociographiques, 2011)
Number: 2
Keywords: Caricature

L'atelier d'orfèvrerie de Gilles Beaugrand - Vaillancourt, Éric (Université Laval, 2011)
Keywords: Orfèvres

The Living Monument: A Consideration of the Politics of Indigenous Representation and Public Historical Monuments in Québec - Wilkinson, Sarah A. (Université Concordia, 2011)
Keywords: Autochtones; Monuments; Places publiques

Victoria Avenue in Westmount (The Westmount Historian, 2010)
Number: 1
Keywords: Casernes; Gares; Logement; Magasins; Rues; Westmount; Épicerie

Photography as History (The Westmount Historian, 2010)
Number: 2
Keywords: Notman; William; Photographie

La commande publique dans un contexte de diversité ethnoculturelle: débat entourant l'érection du monument La réparation (1994-1998) - Alvarez Hernandez, Analays (Université du Québec à Montréal, 2010)
Keywords: Arméniens; Monuments; Turcs

Ressemblance et caractère dans les portraits de Théophile Hamel (1840-1870) - Aubé-Gaudreau, Adrienne (Université Laval, 2010)
Keywords: Peinture

Trajectoires, circulation, assemblages: des modes hétérogènes de la constitution de la pratique en arts numériques à Montréal - Charrieras, Damien (Université de Montréal et Université Sorbonne Nouvelle - Paris 3, 2010)

Andy Warhol at Expo 67: Pop In and Pop Out - Côté, Jean-François (Expo 67: Not Just a Souvenir, 2010)
Keywords: Expositions

La culture artistique au Québec au seuil de la modernité: Jean-Baptiste Lagacé, fondateur de l'histoire de l'art au Canada - Hazan, Olga (Septentrion, 2010)
Keywords: Commission des écoles catholiques de Montréal; Lagacé; Jean-Baptiste; Université de Laval à Montréal

Dossier: Histoire du meuble - Loubert, Huguette; Ouellet, Richard (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2010)
issued: 2010-24-00/2011-24-00
Keywords: Artisans; Plateau Mont-Royal; Quartiers; Sculpture; Ébénistes

Penser l’éducation artistique et pratiquer le design graphique. Historique de la formation en design graphique au Québec avant 1970 - Mélançon, Alain (Université de Sherbrooke, 2010)
Keywords: Imprimerie; Université du Québec à Montréal; École des Beaux-Arts; École des arts graphiques; École technique

La réception des expositions d'art engagé à la fin du XXe siècle au Québec: entre reconnaissance et institutionnalisation - Melançon, Catherine (Université de Montréal, 2010)
Keywords: Expositions; Musée d’art contemporain de Montréal; Musées

The Tools of Engagement: Tactics and Strategies Employed for the Creation of Alternative Places, Spaces, and Modes of Citizenship within the Montreal Graffiti Subculture - Murray, Kristopher (Université Concordia, 2010)

Variations colorées d’une pratique mondialisée: l’appropriation culturelle du graffiti hip-hop à Montréal et à São Paulo - Proulx, Raphaëlle (Université de Montréal, 2010)

The Ambiguous Modernity of Designer Julien Hébert - Racine, Martin (Expo 67: Not Just a Souvenir, 2010)

Renaissance Art in Montreal: The City's Early Collectors and Their Gifts to the Art Association of Montreal and the Montreal Museum of Fine Arts - Sorbelli, Silvia (Université Concordia, 2010)
Keywords: Art association; Musée des Beaux-Arts; Musées

Napoléon Bourassa et la vie culturelle à Montréal au XIXe siècle - Vallée, Anne-Élisabeth (Leméac, 2010)
Keywords: Art association; Bourassa; Napoléon; Peinture; Sculpture; École des Beaux-Arts

Pictures of Health: SickKids Exposed - Adams, Annmarie; McKeever, Patricia; Theodore, David (Depicting Canada's Children, 2009)
Keywords: Children's Memorial Hospital; Enfants; Hôpitaux; Photographie; Royal Victoria Hospital; Tuberculose; Épidémies

Adrien Hébert: de la réalité à la représentation: étude des scènes de rues de Montréal (1925-1940) - Beaulne, Caroline (Université du Québec à Montréal, 2009)
Keywords: Hébert; Adrien; Peinture

Jean-Paul Mousseau artiste public: étude de la station de métro Peel, de l'église Saint-Maurice-de-Duvernay et de la Mousse spacthèque de Montréal - Bradette Brassard, Judith (Université du Québec à Montréal, 2009)
Keywords: Transport en commun; Églises

Un héritage méconnu: les tableaux de l'ancienne église Notre-Dame de Montréal - Des Rochers, Jacques (Éditions de la Fabrique de la paroisse Notre-Dame de Montréal, 2009)
Keywords: Arts sacrés; Notre-Dame (église); Peinture; Églises

Le musée de François Hertel ou la chute du philosophe - Dubé, Philippe (1937: un tournant culturel, 2009)
Keywords: Hertel; François (Rodolphe Dubé; père); Musées

L'Arche: un atelier d'artistes dans le Vieux-Montréal - Foisy, Richard (VLB, 2009)
Keywords: Quartiers; Vieux-Montréal

Un modernisme de bon aloi: réception critique et politique de la caricature en 1937 - Hardy, Dominic (1937: un tournant culturel, 2009)
Keywords: Caricature

Gilles Corbeil (1920-1986), un ‘passeur’ tranquille - Lacroix, Laurier (Les Cahiers des Dix, 2009)
Number: 63
Keywords: Expositions; Peinture

Les barbares, nos premiers modernes ou "Comment New York a volé..." au secours de l'art moderne dans la province de Québec - Lacroix, Laurier (1937: un tournant culturel, 2009)
Keywords: Peinture

Museums as Communal Spaces - McMaster, Jenny (Université Concordia, 2009)
Keywords: Musées

Sortir de l'impasse patrimoniale: l'Inventaire des oeuvres d'art - Morisset, Lucie K.; Noppen, Luc (1937: un tournant culturel, 2009)
Keywords: Patrimoine

The Automatiste Revolution: Montreal, 1941-1960 - Nasgaard, Roald; Ellenwood, Ray (Douglas & McIntyre, 2009)
Keywords: Automatistes

Montréal, du fleuve à la montagne par l'art urbain - Proulx, Denis (Montréal, aujourd'hui et demain. Politique, urbanisme, tourisme, 2009)

Art québécois moderne (depuis 1940) au musée: regard sur la mise en scène permanente des collections - Richer, Angèle (Université de Montréal, 2009)
Keywords: Musée des Beaux-Arts; Musée d’art contemporain de Montréal; Musées

L'iconographie rébellienne, la face cachée de l'historiographie des rébellions de 1837-1838: quelques études de cas - St-Jean, France (Mens, 2009)
issued: 2009-23-00
Keywords: Histoire; Rébellions

Autour de 1937. Modernité artistique et culture de masse: un rendez-vous manqué? - Trépanier, Esther (1937: un tournant culturel, 2009)
Keywords: Peinture

Le nez de Maurice Duplessis. Le Québec des années 1940 tel que vu, représenté et raconté par Robert La Palme: analyse d'un système figuratif - Turgeon, Alexandre (Université Laval, 2009)
Keywords: Caricature

La contribution artistique, pédagogique et théorique de Napoléon Bourassa à la vie culturelle montréalaise entre 1855 et 1890 - Vallée, Anne-Élisabeth (Université du Québec à Montréal, 2009)
Keywords: Art association; Bourassa; Napoléon; Peinture; Sculpture; École des Beaux-Arts

Peinture et territoire en dialogue. Regard de Paul-Émile Borduas sur l’Amérique - Vigneault, Louise (Mens, 2009)
issued: 2009-23-00
Keywords: Borduas; Paul-Émile; Peinture

La "Collection Suzor-Côté" au Musée de l'Amérique française: image de l'artiste et de son atelier et leur rôle dans l'atteinte de la renommée artistique - Beaulieu, Geneviève (Université Laval, 2008)
Keywords: Musées; Peinture

Les ateliers d’artistes dans l’écosystème montréalais: Une étude de localisation - Bellavance, Guy; Latouche, Daniel (Recherches sociographiques, 2008)
Number: 2

Ut Pictura Poesis: Edward Black Greenshields' Collection of Hague School Paintings - Buis, Alena M. (Université Concordia, 2008)
Keywords: Peinture

Omer DeSerres. Trois générations créatives - DeSerres, Hélène (Éditions de l'Homme, 2008)
Keywords: Magasins

The Pictured and the Posed: Nineteenth Century Touristic Images of the Lachine Rapids - Eagan, Mireille M. (Université Concordia, 2008)
Keywords: Lachine; Paysages; Peinture; Photographie; Tourisme

Design, Presentation Silver and Louis-Victor Fréret (1801-1879) in London and Montreal - Fox, Ross (Material Culture Review / Revue de la culture matérielle, 2008)
Pas dans la période V car il n'est pas à Montréal avant 1867 de ce que nous (JRL) comprenons
issued: 2008-21-00
Keywords: Artisans; Sculpture

Mira Godard: Canada's Art Dealer - Fyfe, Heather Dianne (Université Concordia, 2008)
Keywords: Expositions

Théophile Hamel: peintre (1817-1870) - Hamel-Beaudoin, Françoise (Lidec, 2008)
Keywords: Peinture

Formation artistique et contexte social des peintres canadiens à Paris (1887-1895) - Leblanc, Marie Chantal (Université du Québec à Montréal, 2008)
Keywords: Peinture

Un artiste au quotidien au tournant du XXe siècle: le cas de Ludger Larose, 1868-1915 - Longstaff, Alison (Université du Québec à Trois-Rivières, 2008)
Keywords: Bourgeoisie; Francophones; Francs-Maçons; Peinture

Tourisme et vulgarisation historique dans le milieu artistique montréalais entre les années 1910 et 1930: étude des recueils Old Montreal d'Herbert Raine et Le Vieux Montréal historique de Georges Delfosse et Croquis Montréalais de Charles Walter Simpson - Matte, Gabrielle (Université du Québec à Montréal, 2008)
Keywords: Histoire; Quartiers; Tourisme; Vieux-Montréal

Construction de la valeur de l'objet d'art dans les monographies paroissiales au Québec de 1854 à 1925 - Miglioli, Nathalie (Patrimoine et sacralisation, 2008)
Keywords: Arts sacrés; Églises

Une voix féminine dans l’espace public. La Galerie Dominion, 1941-1956 - Pageot, Édith-Anne (Globe: revue internationale d'études québécoises, 2008)
Number: 2
Keywords: Femmes; Peinture

Jewish Painters of Montreal: Witnesses of Their Time, 1930-1948 - Trépanier, Esther (Éditions de l'Homme, 2008)
Translators: _:n10312
Keywords: Juifs; Peinture

Peintres juifs de Montréal: témoins de leur époque, 1930-1948 - Trépanier, Esther (Éditions de l'Homme, 2008)
Keywords: Juifs; Peinture

Gouverner l'innovation, entre sciences dures et arts plastiques: le consortium interuniversitaire Hexagram (Montréal, Canada) - Fourmentraux, Jean-Paul (Canadian Review of Sociology / Revue canadienne de sociologie, 2007)
Number: 4

Le peintre Rodolphe Duguay et la Montée Saint-Michel - Dagenais, Jean-Guy (Il était une fois... Montréal-Nord, 2007)
issued: 2007-22-00
Keywords: Clubs; Peintres de la Montée Saint-Michel; Peinture; Rues

L'essor du livre illustré au Québec en relation avec les milieux artistiques et éditoriaux français: 1880-1940 - Danaux, Stéphanie (Université de Montréal et Université de Poitiers, 2007)
Keywords: Édition

Stratégies culturelles sulpiciennes: les beaux-arts - Des Rochers, Jacques (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Sulpiciens

Les Sulpiciens au Canada - Dickinson, John A.; Da Silva-Gauthier, Angélique (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Sulpiciens

La place des femmes dans la Société d'art contemporain: Montréal, 1939-1948 - Fortin, Nathalie (Université du Québec à Montréal, 2007)
Keywords: Femmes; Société d'art contemporain

A City's Museum: A History of the Montreal Museum of Fine Arts - Germain, Georges-Hébert (Musée des Beaux-arts de Montréal, 2007)
Translators: _:n56618 Translators: _:n57240
Keywords: Art association; Musée des Beaux-Arts; Musées

Un musée dans la ville. Une histoire du Musée des Beaux-arts de Montréal - Germain, Georges-Hébert (Musée des Beaux-arts de Montréal, 2007)
Keywords: Art association; Musée des Beaux-Arts; Musées

L’art dans le métro: prochaine station: restauration - Lepage, Michèle (Continuité, 2007)
issued: 2007-22-00
Keywords: Transport en commun

The Club Art Collection / La Collection d'oeuvres d'art du Club - Murphy, Sean B. (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; Peinture; University Club; Université McGill

Mobilier québécois au MBAM: regards dans le temps et l’espace - Pepall, Rosalind (Continuité, 2007)
issued: 2007-24-00/2008-24-00
Keywords: Musée des Beaux-Arts; Musées

Pastorale et prédication - Rousseau, Louis (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Sulpiciens

Les photographes québécois: la première liste officielle (1839-1950) - Allard, Jean-Luc; Poitras, Jacques (Éditions historiques et généalogiques Pépin, 2006)
Keywords: Photographie

The Architecture and Painting Collection of the Mount Royal Club Montreal 1899-1920 - Banham, Kathryn J. (Université Concordia, 2006)
Keywords: Clubs; Mount Royal Club; Peinture

A Metropolitan Line: Robert LaPalme (1908-1997): Caricature and Power in the Age of Duplessis (1936-1959) - Hardy, Dominic Llywelyn (Université Concordia, 2006)
Keywords: Caricature

Art and the Museum: The Educational Partnership between a Museum and a School - Kader, Laurie (Université Concordia, 2006)
Keywords: Musée d’art contemporain de Montréal; Musées

Le séjour montréalais du graveur français Rodolphe Bresdin, 1873-1877 - Lacroix, Laurier (Les Cahiers des Dix, 2006)
Number: 60
Keywords: Gravure

Est-on quitte envers le passé? Borduas, Vadeboncoeur et le dénouement de « notre maître, le passé » - Lamonde, Yvan (Les Cahiers des dix, 2006)
Number: 60
Keywords: Borduas; Paul-Émile; Idéologies; Peinture

En marge, les circuits des livres d'artistes à Montréal après 1980 - Morin, Marie-Josée (Université de Montréal, 2006)

S’annoncer mur à mur - Paquet, Denis (Continuité, 2006)
issued: 2006-24-00/2007-24-00
Keywords: Conservation; Enseignes; Patrimoine

Des statues en habit de métal - René-Morissette, Jérôme (Continuité, 2006)
issued: 2006-23-00
Keywords: Sculpture

Pneumothorax Then and Now - Adams, Annmarie; Schwartzman, Kevin (Space and Culture, 2005)
Number: 4
Keywords: Children's Memorial Hospital; Hôpitaux; Médecine; Photographie; Tuberculose; Épidémies

Films on Art and/or Art on Film: Jacques Giraldeau's Cinematic Vision of the 1960s - Benguigui, Linda (Université Concordia, 2005)
Keywords: Cinéma

"A Shift of Modality": Postminimal Montreal Sculpture in the 1970s - Bisciglia, Alessandra (Université Concordia, 2005)
Keywords: Champagne; Jean-Serge; Dutkewych; Andrew; Sculpture

La nature morte au Québec et la question du sujet en art (1887-1907) - D'Amours, Annie (Université Laval, 2005)
Keywords: Peinture

Vandalism and Public Art in Montreal: A Discussion of Works by Mark Lewis and Robert Prenovault - Drvar, Tanina (Université Concordia, 2005)
Keywords: Monuments; Places publiques

BORDUAS, PAUL-ÉMILE - Gagnon, François-Marc (Dictionnaire biographique du Canada, 2005)

Charles Gill (1871-1918). Poète en peinture et peinture en poésie - Hamel, Réginald (La Vie culturelle à Montréal vers 1900, 2005)
Keywords: Gill; Charles; Peinture; Poésie

Henri Julien, "ce diable d'homme" - Hardy, Dominic (La Vie culturelle à Montréal vers 1900, 2005)
Keywords: Caricature; Julien; Henri

Bending the Rules: The Montreal Branch of the Woman's Art Association of Canada, 1894-1900 - Haskins, Victoria (Université Concordia, 2005)
Keywords: Art association; Femmes

Art, identité et Expo 67. L'expression du nationalisme dans les œuvres des artistes québécois du Pavillon de La Jeunesse à l'Exposition universelle de Montréal - Hellman, Michel (Université McGill, 2005)
Keywords: Expositions; Nationalisme

MASSICOTTE, EDMOND-JOSEPH - Karel, David (Dictionnaire biographique du Canada, 2005)

L'art au service de "l'utile et du patriotique" - Lacroix, Laurier (La Vie culturelle à Montréal vers 1900, 2005)

Des murs aux trains. Des graffiteurs de Montréal - Le Coroller, Frank (Globe: revue internationale d’études québécoises, 2005)
Number: 2

La formation professionnelle des ouvriers des métiers du livre au Québec au XXe siècle - Leroux, Éric (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2005)
issued: 2005-21-00
Keywords: Imprimerie; École des arts graphiques; École technique

L'École littéraire et la tentation symboliste - Martin, Suzanne (La Vie culturelle à Montréal vers 1900, 2005)
Keywords: École littéraire de Montréal

Imperialist Intent: Lord Strathcona's Art Collection in Nineteenth-Century Montreal - Pierce, Alexandria (Montreal-Glasgow, 2005)
Keywords: Smith; Donald

TOPLEY, WILLIAM JAMES - Rodger, Andrew (Dictionnaire biographique du Canada, 2005)

L'histoire par l'image: commémoration picturale, pouvoir politique et stratégies visuelles au Québec (1880-1930) - Roy, Nathalie Anne (Université McGill, 2005)

La réception critique des nus de Marc-Aurèle de Foy Suzor-Cote (1869-1937) - Saint-Georges, Sylvie (Université du Québec à Montréal, 2005)
Keywords: Art association; Expositions; Peinture

Atlantic Iconography: Images of the St Lawrence-Clyde Passengers Liners of the Canadian Pacific Railway. - Stevenson, Iain (Montreal-Glasgow, 2005)
Keywords: Canadien Pacifique; Chemins de fer

A Little on the Wild Side: Eaton's Prestige Fashion Advertising Published in the Montreal Gazette, 1952-1972 - Bosnitch, Katherine (Fashion. A Canadian Perspective, 2004)
Keywords: Eaton; Montreal Gazette; Publicité

Cultivating Heroes: From Dante and Caboto to Mussolini, the Public Art of Montreal's Italians in the 1920s-1930s - Carlevaris, Anna Maria (Université Concordia, 2004)
Keywords: Italiens; Monuments; Peinture; Sculpture

Les trésors de l'atelier pointelier de Urbain Brien dit Desrochers (1781-1860), sculpteur ornemaniste - Desjardins, Pierre (Atelier d'histoire de la Pointe-aux-Trembles, 2004)
Keywords: Arts sacrés; Sculpture

"Retour à l'ordre" parisien: source de la modernité artistique québécoise - Desmeules, Michelle (Université Laval, 2004)

Le devenir de l'art d'église des paroisses catholiques du Québec: architecture, arts, pratiques, patrimoine (1965-2002) - Gauthier, Richard (Université Laval, 2004)
Keywords: Arts sacrés; Églises

Graffitis signés: analyse sociologique des tags à Montréal - Goulet, Mylène (Université du Québec à Montréal, 2004)

L'aventure artistique du peintre de Saint-Denys Garneau - Huot, Giselle (Mens, 2004)
issued: 2004-21-00
Keywords: Peinture; de Saint-Denys Garneau; Hector

Max Stern, marchand et mécène à Montréal - Musée des beaux-arts de Montréal (Musée des beaux-arts de Montréal, 2004)
Keywords: Expositions; Musée des Beaux-Arts; Musée d’art contemporain de Montréal; Musées

Peindre à gauche - Trépanier, Esther (Bulletin d'histoire politique, 2004)
issued: 2004-23-00
Keywords: Peinture

Le rôle de la médiation culturelle dans la perception de l'art chez les adolescents: étude de cas au Musée d'art contemporain de Montréal - Bonnardot, Delphine (Université du Québec à Montréal, 2003)
Keywords: Musée d’art contemporain de Montréal; Musées

Une imagerie urbaine signifiante : les cartes postales montréalaises et la construction de «monuments» - Caron, Isabelle (Journal of the Society for the Study of Architecture in Canada/Journal de la société pour l’étude de l’architecture au Canada, 2003)
Number: 3-4
Keywords: Paysages

Le paysage attribué à Nicolas Poussin du Musée des beaux-arts de Montréal - Dulude, François-Michaël (Université de Montréal, 2003)
Keywords: Musée des Beaux-Arts; Musées

To Lend the Dead a Voice: Second-Generation German Visual Art - Kessin, Katja (Université Concordia, 2003)
Keywords: Allemands; Juifs

La collection muséale d'art contemporain aux limites du pluralisme et du syncrétisme identitaire - Lévesque, France (Université du Québec à Montréal, 2003)
Keywords: Musée d’art contemporain de Montréal; Musées

Patrimoine industriel: le souffle de l’art - Lord, Denis (Continuité, 2003)
issued: 2003-21-00
Keywords: Patrimoine

After Notman: Montreal Views - A Century Apart / D'après Notman: Regards sur Montreal - Un siècle plus tard - Maciejewski, Andrzej (Firefly Books, 2003)
Translators: _:n46500
Keywords: Notman; William; Photographie

Un saint ragaillardi - Mulaire, Bernard (Continuité, 2003)
issued: 2003-21-00
Keywords: Arts sacrés; Conservation; Monuments

Éduquer par l'art public: le monument à Maisonneuve du sculpteur Louis-Philippe Hébert (1850-1917) - Paetsch, Bärbel (Université du Québec à Montréal, 2003)
Keywords: Chomedey de Maisonneuve; Paul de (Maisonneuve; Paul de Chomedey de); Hébert; Philippe; Monuments; Sculpture

Une fenêtre sur la modernité: les Apprentis-sorciers, 1955-1968 - Sabourin, Jean-Guy (VLB, 2003)
Keywords: Théâtre

L'implantation de la galerie d'art à Montréal: le cas de W. Scott & sons, 1859-1914. Comment la révision du concept d'œuvre d'art autorisa la spécialisation du commerce d'art - Sicotte, Hélène (Université du Québec à Montréal, 2003)
Keywords: Expositions; Peinture

Les représentations des Patriotes dans l'art québécois: le cas d'Henri Julien - Thibault, Marianne (Bulletin d'histoire politique, 2003)
issued: 2003-23-00
Keywords: Caricature; Julien; Henri

Otto Dix's Portrait of the lawyer Hugo Simons: German Art for a Canadian Museum - Cousins, Darlene Caroline (Université Concordia, 2002)
Keywords: Allemands; Peinture

Le Mois de la Photo et la mondialisation de la scène artistique - Couture, Francine (Sociologie et sociétés, 2002)
issued: 2002-23-00
Keywords: Photographie

Louise Lemieux Bérubé: Artist in Motion - Edeh, Rosaline U. (Université Concordia, 2002)
Keywords: Artisans; Textile

Louis-Philippe Hébert, 1850-1917. Sculpteur national - Hébert, Bruno (Lidec, 2002)
Keywords: Arts sacrés; Hébert; Philippe; Monuments; Sculpture

La peinture murale à Montréal (1996-2001): identification et analyse d'une production culturelle - Picard, Johanne (Université de Montréal, 2002)

Imperialist Intent - Colonial Response : The Art Collection and Cultural Milieu of Lord Strathcona in Nineteenth-Century Montreal - Pierce, Alexandria (Université McGill, 2002)
Keywords: Smith; Donald

Les églises: lieux de culte et de culture - Vanlaethem, France (Montréal, la ville aux cent clochers. Regards des Montréalais sur leurs lieux de culte, 2002)
Keywords: Arts sacrés; Patrimoine; Sculpture; Vêtements; Églises

Un album du mont Royal (Continuité, 2001)
issued: 2001-23-00
Keywords: Mont Royal

Visual Art/Public Art and Urban Development: A Case Study of Montreal (1967-1992) - Boyce, Margaret (Université McGill, 2001)
Keywords: Centre canadien d'architecture; Jardins; Squares

Les relations incestueuses entre la photographie et l'architecture moderne: la représentation photographique de la Place Ville-Marie entre septembre 1962 et février 1963 - ChampRoux, Nicolas (Université Concordia, 2001)
Keywords: Gratte-ciel; Photographie; Place Ville-Marie

L'exposition Corridart: un cas de controverse esthétique ou politique? - Couture, Francine (Bulletin d'histoire politique, 2001)
issued: 2001-22-00
Keywords: Expositions

Norman Hudon 1929-1997. Une vie comme un arc-en-ciel de couleurs - Hudon, François (Lidec, 2001)
Keywords: Caricature; Peinture

La production d'art sacré de Charles Daudelin de 1964 à 1992 - Lachance, Valérie (Université de Montréal, 2001)
Keywords: Arts sacrés

Guido Nincheri artiste entrepreneur - Laroche, Ginette (Guido Nincheri: un artiste florentin en Amérique, 2001)
Keywords: Arts sacrés; Peinture; Vitraux; Églises

Le vitrail au studio de Guido Nincheri - Laroche, Ginette (Guido Nincheri: un artiste florentin en Amérique, 2001)
Keywords: Arts sacrés; Vitraux; Églises

Guido Nincheri muraliste - Laroche, Ginette; Pellissier, Pierlucio (Guido Nincheri: un artiste florentin en Amérique, 2001)
Keywords: Arts sacrés; Peinture; Églises

Painting on the Edge: Geometric Abstraction in Montreal, the 1950s - Patterson, Jody (Université Concordia, 2001)
Keywords: Peinture

Un don remarquable des Sœurs grises de Montréal: un maître-autel de Philippe Liébert - Béland, Mario (Cap-aux-Diamants, 2000)
issued: 2000-23-00
Keywords: Communautés religieuses; Liébert; Philippe; Soeurs Grises

A Little On the Wild Side: Eaton's Prestige Fashion Advertising Published in the Montreal Gazette, 1952-1972 - Bosnitch, Katherine (Université Concordia, 2000)
Keywords: Eaton; Magasins; Montreal Gazette; Publicité

Les galeries Denyse Delrue (1957-1984) - Marcotte, Julie (Université du Québec à Montréal, 2000)
Keywords: Expositions; Peinture

Forging the Corporate Identity with Art: Four Montreal Corporations: Alcan Aluminium Limited, Martineau Walker, Banque Nationale du Canada, Loto-Quebec with a focus on Alcan - Meade, JoAnn (Université McGill, 2000)

Le comportement de consommation artistique et culturel des groupes ethniques à Montréal, le cas des Portugais, des Maghrébins et des Italiens - Paiement, Isabelle (Université du Québec à Montréal, 2000)
Keywords: Italiens; Maghrébins; Portugais